Patient- and Family-Centered Care in the Preoperative Setting: Simulation Cases Featuring Standardized Patients for Anesthesia Residents - Jill H. Irby; Michael E. Anders; Drew A. Beasley; Julie Moretz; Barbara Brunner (Association of American Medical Colleges, 2017)
Introduction Evidence links patient-centered care to improvements in allocation of health care resources, patient satisfaction, chronic disease self-management, morbidity, and mortality. Support from families, too, can improve patients' health and well-being. However, patient- and family-centered care (PFCC) in the preoperative setting is challenging due to short-term relationships with patients, time constraints, and lack of training. Methods This module uses simulations with standardized patients. Groups of residents are divided into pairs, and each resident in a pair alternately participates in, or observes via live camera feed, a simulation case. The pair participates in both debriefing sessions. Two simulation cases are run. The first features a Jehovah's Witness who wants lifesaving blood but does not want her accompanying daughter to know. Despite excruciating pain, analgesia is being withheld because surgery consent has not been obtained. The second features a patient with HIV who does not want her accompanying pastor to know. The operating room nurse calls for a resident to bring her to surgery, but the patient wants to talk to her mother, who has yet to arrive. The purpose of the curriculum is for anesthesia residents to apply PFCC when having difficult preoperative conversations with patients and their families and obtaining anesthesia consent. Results Participants rated the training environment, faculty, debriefing, clinical application, and contribution of standardized patients highly. Participants' perceived self-efficacy for each core principle of PFCC improved postsimulation compared to presimulation. Discussion We believe this curriculum can contribute to improvement in PFCC and subsequent improvement in the quality and safety of health care.